Impact of multiple channels on the Characteristics of Rectangular GAA MOSFET - Mohammed Khaouani; Ahlam Guen-Bouazza (Institute of Advanced Engineering and Science, 2017)
Square gate all around MOSFETs are a very promising device structures allowing to continue scaling due to their superior control over the short channel effects. In this work a numerical study of a square structure with single channel is compared to a structure with 4 channels in order to highlight the impact of channels number on the device’s DC parameters (drain current and threshold voltage). Our single channel rectangular GAA MOSFET showed reasonable ratio Ion/Ioff of 104, while our four channels GAA MOSFET showed a value of 103. In addition, a low value of drain induced barrier lowering (DIBL) of 60mV/V was obtained for our single channel GAA and a lower value of with 40mv/v has been obtained for our four channel one. Also, an extrinsic transconductance of 88ms/µm have been obtained for our four channels GAA compared to the single channel that is equal to 7ms/µm.